Analisis Permainan Tradisional Untuk Pengembangan Keterampilan Proses Sains Anak Di Desa Ekowisata Pampang Gunungkidul - Wahyuni Fajar Arum; Kartika Fajar Nieamah (STIE Pariwisata API Yogyakarta, 2020)
This study aims to determine (1) the influence of traditional game media on the science process skills of children tourist in Pampang Gunungkidul Yogyakarta ecotourism village and (2) the influence of traditional game media on the social skills of children tourist in the Pampang Gunungkidul Yogyakarta ecotourism village. Research type used in this study is Research and Development. The data collection methods in this study used test, observation, documentation and also interviews. The test methods used in this study pre-test and post test in the form of multiple choice. The conclusions of this study are 1) learning media in the form of traditional games have an influence on science process skills. This is based on the t test carried out on the pre-test and post test data which shows that the velue of t table is 2.04841 while t arichmetic is -14.748. These result indicate that the value of t table > t arithmetic thus, it can be concluded that there is an influence on social skills. This can be seen from the results of the social skills observation which show that tourist who have high social skills have a frequency of 16 people while tourists children who have low social skills have a frequency of 14 people.